Strategi Gaya Kepemimpinan Dalam Upaya Meningkatkan Kinerja Karyawan Pada PT Usaha Baru Gemilang - Deni Leo Aldi; Syifa Pramudita Faddila (Madani: Jurnal Ilmiah Multidisiplin, 2023)
A good leadership style is a leadership style that can motivate subordinates to work. Leadership style strategies provide an important scientific basis for effective leadership development, improve team and organizational performance and assist leaders in dealing with complex challenges and changes in the work environment. The leadership strategy at PT Usaha Baru Gemilang applies more to autocratic leadership in which the leader directs and strictly supervises operational employees to ensure that tasks are carried out as they wish. The writing method used in this research is the Implementative method in the form of descriptive explanations, in which to collect instrument data obtained in research through observation, interviews and documentation. Interviews were conducted with 20 respondents using a list of questions containing questions related to the required data. changing the leadership strategy from autocratic to participatory leadership strategy in which the leader will provide space for his subordinates to be able to participate in a decision and will create an atmosphere of mutual trust between members and leaders.